2005
DOI: 10.1002/app.22182
|View full text |Cite
|
Sign up to set email alerts
|

Nature of compounds formed in phase of strongly basic anion exchanger in contact with Fe2(SO4)3 solutions

Abstract: The thermochemical changes taking place in the phase of a Fe(III)‐containing strongly basic anion exchanger (AV‐17) are investigated by using Mössbauer, IR, and EPR spectroscopy. During the heating of Fe(III)‐containing resin in air up to 200°C, redox processes in the polymer phase take place. On boiling in water, the jarosite‐type compounds in the polymer are converted into higher dispersed β‐FeOOH particles. After sorption–boiling in water cycles in the polymer phase, relatively massive and magnetically orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…However, in certain conditions, polymers of this type are able to retain metallic cations from solutions of Fe(III), Cr(III), and Al(III) sulfates. [1][2][3] Retaining of the M(III)-containing cations on strongly basic anion exchangers from sulfate solutions as a result of anion exchange or M(OH) 3 compounds formation in the polymer phase is unlikely. 3 We have suggested that the retention of the M(III) þ is a functional group of polymer.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, in certain conditions, polymers of this type are able to retain metallic cations from solutions of Fe(III), Cr(III), and Al(III) sulfates. [1][2][3] Retaining of the M(III)-containing cations on strongly basic anion exchangers from sulfate solutions as a result of anion exchange or M(OH) 3 compounds formation in the polymer phase is unlikely. 3 We have suggested that the retention of the M(III) þ is a functional group of polymer.…”
Section: Introductionmentioning
confidence: 97%
“…11 In the phase of strongly basic anion exchangers, when boiling in water media, jarosite compounds may be converted into b-FeOOH in superparamagnetic state or relatively massive magnetically ordered particles. 2,4 Native jarosite mineral is not so stable, partially being transformed into Fe(OH) 3 . 5 It is necessary in order to apply Fe(III)-containing strongly basic anion exchangers as selective sorbents or catalysts to know their behavior in different media and sorption-desorptional features of the Fe(III)-containing cations on such kind of polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, theoretically, they are able to retain from solution only anions but not inorganic cations. However, in previous studies1–3 it has been reported that in certain conditions, strongly basic anion exchangers are able to retain Fe(III), Al(III), Cr(III)‐containing cations (hydroxocomplexes) from solutions. These cations are retained by polymers from their sulfates solutions only and not from nitrates or chlorides.…”
Section: Introductionmentioning
confidence: 99%
“…The retaining of cations takes place through the formation in the polymer phase of jarosite4–6 mineral type compounds: R 4 N[M 3 (OH) 6 (SO 4 ) 2 ] and H 3 O[M 3 (OH) 6 (SO 4 ) 2 ], where R 4 N + is a polymer group, M is Fe 3+ , Al 3+ , or Cr 3+ . In the polymer phase, metallic compounds are in the form of ultra fine particles 1, 7…”
Section: Introductionmentioning
confidence: 99%